Laparoscopic vs modified Lichtenstein surgery in patients operated on for uncplicated inguinal hernia at Carlos Alcántara Butterfield Hospital between november 2015 and february 2019 - Gálvez-Mideiros, Victor (2023)
The purpose of this study was to compare results for surgical repair of uncomplicated inguinal hernia using two different techniques: laparoscopic technique and modified Lichtenstein. Methods: This retrospective, descriptive observational study included 307 patients who underwent surgery for uncomplicated inguinal hernia at Carlos Alcantara Butterfield hospital between november 2015 and february 2019. Of these, 201 underwent surgery using the Lichtenstein technique and 106 were operated using the laparoscopic technique. Primary endpoints included recurrency and chronic pain, labeled as late complications and secondary endpoints were short-term complications including acute pain, seroma, hematoma, cord cyst, surgical wound infection, orchoepididymitis and hydrocele. Results: Of the 307 patents who underwent surgical repair for inguinal hernia. 201 were operated using the Lichtenstein technique and 106 underwent surgery using the laparoscopic technique. Patients were followed-up for 1.07 to 5.5 years. Regarding the primary endpoint, it was found that laparoscopic surgery resulted in less frequency of late complications by 8.7% compared to surgery using the Lichtenstein technique (RP = 0.13, IC 95%: 0.03 - 0.71). No statistical significant difference was found for secondary endpoints between laparoscopic and Lichtenstein techniques.